2003
DOI: 10.1080/1042819031000067585
|View full text |Cite
|
Sign up to set email alerts
|

Poor Mobilization of Peripheral Blood Stem Cells is a Risk Factor for Worse Outcome in Lymphoma Patients Undergoing Autologous Stem Cell Transplantation

Abstract: The effect of poor blood stem cells mobilization on the outcome of autologous stem cell transplantation (ASCT) has not been well studied. Our aim is to evaluate poor mobilization as a prognostic factor in lymphoma patients undergoing ASCT. We analyzed 90 consecutive patients with Hodgkin's (HD) and non-Hodgkin's lymphoma (NHL) who underwent ASCT. Poor mobilization was defined as the inability to obtain > or = 1 x 10(6) CD34+ cells/kg ideal body weight with two large volume aphereses. Patients were divided into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
82
1
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 20 publications
7
82
1
1
Order By: Relevance
“…This is in accordance with two retrospective analyses strongly suggesting that lymphoma patients with poor mobilization have worse outcomes. 8,9 A third study showed no difference in event free and OS but a trend towards increased early death in the cohort of poor mobilizers. 10 Chemotherapy mobilization has been observed to yield larger numbers of CD34 þ progenitors than mobilization with G-CSF alone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in accordance with two retrospective analyses strongly suggesting that lymphoma patients with poor mobilization have worse outcomes. 8,9 A third study showed no difference in event free and OS but a trend towards increased early death in the cohort of poor mobilizers. 10 Chemotherapy mobilization has been observed to yield larger numbers of CD34 þ progenitors than mobilization with G-CSF alone.…”
Section: Discussionmentioning
confidence: 99%
“…Three other studies have reported similar results, although none have been able to compare outcomes of different mobilization techniques. [8][9][10] A study from Stanford included 170 NHL patients mobilized with chemotherapy and G-CSF receiving purged autografts and reported no difference in the 3 year OS and event-free survival (EFS) between patients collecting greater or less than 2 Â 10 6 CD34 þ cells/kg. 10 Similar to our results, patients with poor mobilization had delayed engraftment and women were more likely to be poor mobilizers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,15 In some studies, higher stem cell doses have been associated with higher rates of survival for patients. 17,18 Other factors that affect collection efficiency and, therefore, the success of auto-HSCT include patient age, gender, exposure to previous irradiation and chemotherapy, previous mobilization attempts and disease characteristics such as the involvement of BM. [19][20][21] Unsuccessful initial stem cell mobilization leads to costly additional mobilization attempts and may prohibit auto-HSCT altogether.…”
Section: Introductionmentioning
confidence: 99%
“…Poor mobilization is a risk factor for worse outcome. 14 Patients mobilizing larger numbers of CD34 þ cells have improved survival following autologous transplantation for lymphoma. 15,16 VP-16 with G-CSF is an effective and useful method of mobilization in patients with lymphomas.…”
Section: Discussionmentioning
confidence: 99%